Again I see the gaillardias - Li, Tong 1953-2004 (Balestier Press, 2016)
Through misunderstanding, sympathy, reconciliation and love, seven schoolchildren forged an abiding friendship in their hometown Penghu, a cluster of islands in the Taiwan Strait. Brought together by their Arts and Crafts teacher, the children learned to cherish their friendship and to understand their cultural roots. At their farewell party, they promised to come back for a reunion twenty years later, on the evening of the Mid-Autumn Festival. Now working in Canada, Glasses is coming home to keep his promise. Penghu’s landscapes – waves, fields, cows, coral-stone walls, horsetail trees and gaillardias – summon back memories at school, in the pottery workshop, and on a trip to the Isle of Jibei. As he makes his way towards the old workshop, Glasses relives those memories and contemplates the meaning of home
Keywords: Friendship / Fiction; Friendship; Fiction; Kinderbuch